2017
DOI: 10.2135/cropsci2017.02.0096
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Management, Nitrogen Use Efficiency, and Seed Yield and Quality of Creeping Signalgrass

Abstract: Nitrogen (N) fertilization management can affect the seed yield and quality of tropical forage grasses. Studies have shown the effect of N rates on tropical grass seed production, but no study has evaluated the effect of application timing of N on the N use efficiency (NUE) and seed yield and quality of creeping signalgrass [Urochloa humidicola (Rendle) Morrone & Zuloaga, syn. Brachiaria humidicola (Rendle) Schweick.]. Field experiments were conducted over two growing seasons in Santo Anastácio, São Paulo, Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Hopkinson et al (1996) considered that seed weights <450 mg 100 seeds -1 indicate low percentage of mature seeds in signal grass. Other studies have shown that application of N can influence mean seed weight in signal grass (Carmo et al 1988) and creeping signal grass (Urochloa humidicola (Rendle) Morrone & Zuloaga) (Catuchi et al 2017). However, little is known about the physiological basis for these observations.…”
Section: Discussionmentioning
confidence: 99%
“…Hopkinson et al (1996) considered that seed weights <450 mg 100 seeds -1 indicate low percentage of mature seeds in signal grass. Other studies have shown that application of N can influence mean seed weight in signal grass (Carmo et al 1988) and creeping signal grass (Urochloa humidicola (Rendle) Morrone & Zuloaga) (Catuchi et al 2017). However, little is known about the physiological basis for these observations.…”
Section: Discussionmentioning
confidence: 99%
“…Tupi accumulated less leaf mass than other grasses and this did not vary with season, while Marandu and Guará increased leaf accumulation when environmental conditions were more favorable (Figure 1). Tupi also had the greatest stem proportion because of its growth habit, with many tillers resulting in greater herbage bulk density (Catuchi et al., 2017; Kalmbacher, Adjei, Ezenwa, & Martin, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen is one of the nutrients that accumulates in high amounts in the aboveground tropical perennial forage grasses (Primavesi et al, 2006;Moreira et al, 2013;Costa et al, 2015). Nitrogen supply to tropical forage grasses increases herbage yield, as well as the yield components (number of reproductive tillers, inflorescence, length, numbers of seed per inflorescence, and seed filling), seed yield (Manarim & Monteiro, 2002;Barth Neto et al, 2010;Canto et al, 2012;Catuchi et al, 2017), and seed quality (weight and germination) (Canto et al, 2012;Catuchi et al, 2017). However, excess N supply or its application at inappropriate development phases can reduce the yield and quality of tropical forage grass seeds (Condé & Garcia, 1988;Barth Neto et al, 2010;Catuchi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This occurs because plants allocate nutrients for vegetative biomass production (Condé & Garcia, 1988;Viana et al, 2011;Cecato et al, 2014). Therefore, to increase the production of tropical forage grass seeds, the application of part of N at the beginning of the reproductive phase (after panicle initiation) may be advantageous, since in this phase, the source-sink ratio of the plant occurs, and photoassimilates, which would previously be translocated to the growth of tillers and leaves, are redistributed to the reproductive structures (Condé & Garcia, 1988;Basto, 2014;Catuchi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation